The use of species-specific primer targeting on D-loop mitochondrial for identification of wild boar meat in meatball formulation - Arini, Rien Larasati; Ramadhani, Dwiky; Pebriyanti, Ni wayan; Sismindari, Sismindari; Rohman, Abdul (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The study was intended to design the new specific primer targeting on mitochondrial D-Loop gene (D-Loop 443 primer) combined with a real-time polymerase chain reaction (PCR) for the analysis of wild boar meat (WBM) in food products of meatball. Materials and methods: The primer was designed and subjected to primer-basic local alignment search tool using National Center for Biotechnology Information software. Validation of real-time PCR using designed primer was performed by evaluation of several performance characteristics which included specificity, sensitivity, repeatability, linearity, and efficiency. Results: The results showed that the D-loop primer could be attached at 60.7°C and no amplification was detected against other species confirming the specificity of the primers. The limits of detection were found to be 4.68 ng and 2.34 ng using DNA extracted from WBM and that extracted from wild boar in meatball product. The D-Loop 443 primer was successfully used for the analysis of commercial meatball samples. Conclusion: The developed method can be proposed as a standard method for the identification of WBM in meatball to support halal products authentication. http://doi.org/10.5455/javar.2018.e275